The democracy cookbook : recipes to renew governance in Newfoundland and Labrador - Moore, Lisa, 1964-; Marland, Alex, 1973- (Social and economic papers, 2017)
"The Democracy Cookbook is a collection of short and snappy, non-partisan opinion pieces authored by a cross-section of opinion leaders, academics, and citizens. A unique form of grassroots mobilization, this book brings together a wide variety of voices to speak to the matter of "fixing" democratic governance in Newfoundland and Labrador after a period of acute political turmoil. The goal of the book is to propel debate about what needs to change with respect to democratic governance in Newfoundland and Labrador."--